Effect of citric acid pretreatment time on the characteristics of halal gelatin derived from manyung fish (Arius thalassinus) bones - Yanuba, Vadya Kautsar; Afifah, Ika Qurrotul (Universitas Airlangga, 2025)
Global market demand for gelatin products is expected to continue to increase by 4.3% during the period 2022-2030, but it is not matched by the availability of raw materials for making halal gelatin. In this research, the isolation and characterization of gelatin from manyung fish (also known as giant sea catfish) bones (Arius thalassinus), which has the potential to be an alternative in meeting the needs of halal gelatin. The purpose of this study was to identify the presence of typical gelatin absorption in the FTIR results of isolation products from manyung fish bones (Arius thalassinus) and determine the effect of variations in the length of citric acid soaking in the pretreatment stage on the yield and gelatin characteristics. Pretreatment was carried out using 9% citric acid solution, varying lengths of soaking: 24 hours, 48 hours, 72 hours, and 96 hours. Gelatin was then extracted twice at 70°C for 6 hours. Characterization included functional group analysis, pH, moisture content, gel strength, and viscosity. Analysis using an FTIR spectrophotometer showed the presence of typical absorption of gelatin functional groups in the form of amide A, amide I, amide II, amide III, and finger-print. The results showed that the soaking time significantly affected the yield, pH, gel strength, and viscosity of the produced gelatin, but did not significantly impact the moisture content of the gelatin. The yield of manyung fish bone gelatin ranged from 5.847-15.530%. The pH value ranged from 4.698-4.078, the moisture content 5.588-6.412%, viscosity 0.926-1.870 cP, and gel strength 183.990-55.077 g bloom. The test results of pH, moisture content, viscosity, and gel strength have met the quality standards of GMIA 2019 and SNI 06-3735-1995. The yield, moisture content, pH, viscosity, and gel strength of manyung fish bone gelatin were significantly influenced by the length of pretreatment time used Keywords: Citric Acid, Halal Gelatin, Manyung Fish Bones, Pretreatment Time